A tool to benchmark the food safety management systems in Greece. Issue 8 (29th November 2018) - Souliotis, Andreas; Giazitzi, Katerina; Boskou, George
Abstract : Purpose: The purpose of this paper is to develop and implement methods to benchmark the food safety and hygiene of different companies, regardless the management systems applied. Design/methodology/approach: The data were collected using a balanced questionnaire which was based on the fishbone model of Ishikawa. The questionnaire includes general questions about the company and 25 questions about personnel, machinery, materials, methods and environment. It was applied to 202 food industries, 42 food retail businesses and 49 food service companies. The data were collected from interviews of industry people related to food safety and from audits of business facilities. The benchmarking methods were descriptive statistics, radar charts, cluster analysis and association rules. Findings: The radar charts were used to benchmark food companies on safety and hygiene. Food companies can be evaluated with this benchmarking tool with a balanced score of maximum 100 points. Originality/value: This benchmarking tool could be useful for food control authorities, clusters of companies and certification bodies.